2016
DOI: 10.1186/s12974-016-0489-7
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme 2 activator diminazene aceturate prevents lipopolysaccharide-induced inflammation by inhibiting MAPK and NF-κB pathways in human retinal pigment epithelium

Abstract: BackgroundRetinal inflammation is a devastating pathological process in ocular diseases. Functional impairment of retinal pigment epithelium (RPE) is associated with inflammatory retinal diseases. Enhancing the protective axis namely ACE2/Ang-(1-7)/Mas by activation of ACE2 presents anti-inflammatory properties. We investigated whether diminazene aceturate (DIZE), an angiotensin-converting enzyme 2 (ACE2) activator, prevented lipopolysaccharide (LPS)-induced inflammatory response by activating the protective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(52 citation statements)
references
References 45 publications
4
47
0
1
Order By: Relevance
“…In the present study, the stimulation of Ang-(1-7)/Mas axis revealed itself as an alternate strategy to minimize the impact of IL-1β on human VSMC pro-inflammatory activation. This is in line with other reports showing that in the context of neuroinflammation the pharmacological activation of the ACE2/Ang-(1-7) can reduce the inflammatory response of human retinal pigment epitelial cells to lipopolysaccharide (Tao et al, 2016). Furthermore, Ang-(1-7) may prevent the inflammation induced in astrocytes by physical stressors, such as radiation (Moore et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the stimulation of Ang-(1-7)/Mas axis revealed itself as an alternate strategy to minimize the impact of IL-1β on human VSMC pro-inflammatory activation. This is in line with other reports showing that in the context of neuroinflammation the pharmacological activation of the ACE2/Ang-(1-7) can reduce the inflammatory response of human retinal pigment epitelial cells to lipopolysaccharide (Tao et al, 2016). Furthermore, Ang-(1-7) may prevent the inflammation induced in astrocytes by physical stressors, such as radiation (Moore et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Recent study shows that diabetic microvascular complications can be prevented and reversed by overexpressing the ACE2 level in diabetic rodent retina [72]. Another study reported that the inflammatory response induced by lipopolysaccharide in retinal pigment epithelium (RPE) cells were decreased with diminazene aceturate (DIZE, an ACE2 activator) treatment [73]. They also found that DIZE reduced the expression of Ang II and AT1R, whereas it increased the Ang-(1-7) level in RPE cells.…”
Section: Ace2/ang-(1-7)/mas Receptor Axis In Drmentioning
confidence: 99%
“…67 In line with our previous studies, activation of the ACE2/Ang-(1-7)/Mas axis downregulated phosphorylation of MAPKs and NF-jB signaling. 33,36 These data indicated that ACE2 may ameliorate the inflammatory response by regulating MAPKs and NF-jB pathways.…”
Section: Ace2 Reduces Ab-induced Inflammation In Human Rpementioning
confidence: 90%
“…[27][28][29][30] Most components of RAS, including ACE2/Ang-(1-7)/Mas axis, have been confirmed in various tissues and organs, including the eye. 21,31,32 Our previous study showed that activation of ACE2 alleviated the lipopolysaccharide (LPS)-induced inflammatory response in both human RPE cells 33 and in endotoxin-induced uveitis (EIU) mouse/rat models. 34,35 Moreover, the most recent study from our laboratory demonstrated that adeno-associated virus (AAV)-mediated ACE2 gene delivery alleviated the ocular inflammation in experimental autoimmune uveitis (EAU) mouse model by activating the local ACE2/Ang-(1-7)/Mas axis.…”
Section: 20mentioning
confidence: 99%
See 1 more Smart Citation